Studies on Ibn Khaldun by Muslim Scholars in Malaysia - Ab Hamid, Norafifah; Hamat, Mohd Fauzi; Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Ibn Khaldun is undoubtedly a renowned figure in Malaysia’s Islamic context. His outstanding attributes have always been highlighted in numerous studies among Muslim scholars in Malaysia. Hence, this study aims to identify the previous studies on Ibn Khaldun by Malaysian Muslim scholars. This research is qualitative in nature and it deploys a text analysis method which focuses on studies by Muslim scholars in Malaysia from the year 2000 to 2018. The findings revealed that there are ninety studies from various forms of sources including journal articles, dissertations, theses, conference proceedings, chapters in book and books. This research is a qualitative research design. Document research method is used to gather the data related to Ibn Khaldun from various sources like books, theses, web pages, journals and related papers about Ibn Khaldun. The systematic literature review method is used to assess the studies that have been conducted about Ibn Khaldun. Content analysis method that is used in this research only focused on the studies that are conducted by Muslim scholars in Malaysia from the year of 2000 to 2018. Besides, there are five main research themes on Ibn Khaldun which are thoughts and civilization, thoughts and philosophy, education, economy, and politics. This research is deemed important in order to empower studies on Ibn Khaldun’s attributes which at the same time would contribute towards the expansion of his thoughts in Malaysia.